ROMANIA'S TOURISM OFFER AND DEMAND IN THE COVID-19 PANDEMIC OF 2020 AND 2021 COMPARED TO 2019. A STATISTICAL OVERVIEW - Agatha POPESCU; Cristiana TINDECHE; Alina MĂRCUȚĂ; Liviu MĂRCUȚĂ; Adelaida HONȚUȘ; Mirela STANCIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The goal of the study is to analyze Romania's tourism in the years of the COVID-19 pandemic, 2020 and 2021, in order to quantify the gaps compared to the highest performance achieved in 2019 and in what measure tourism started to recover. Offer in terms of units with function for tourists' accommodation, their number, structure and evolution, number of places and their dynamics by accommodation type, and demand in terms of arrivals, overnight stays both at national level and in rural tourism, index of net use of accommodation capacity, incoming and outgoing tourism were the main studied indicators using fixed basis and structural indices and comparison method. Compared to 2019, in 2021 the number of accommodation units reached 9,146, being by +8.8% higher and the number of places accounted for 364.5 thousand (+2.2%). In 2020, tourist arrivals represented 47.8% and in 2021 accounted for 69.3% of the 2019 level, and the overnight stays followed a similar situation. The main destinations were the seashore, mountain and spa resorts, Romanian tourists having about 90% share in total arrivals. The pandemic was an incentive for Romanians to "Rediscover Romania" and the holiday vouchers were of much help. In a low measure, mainly in 2021, outgoing tourism to Bulgaria, Greece, Turkey, Maldive, Egypt exceeded the incoming tourism. The year 2021 was better than 2020, as the relaxed measures started earlier than in 2020 and tourism managers adopted flexible offers, personalized packages, last minute, early booking, free cancelation, lower tariffs, bonuses etc. The increasing trend is a hope that in 2022 tourism will have a much better dynamics and there are chances to recover!